Sthulta (obesity) an Agnijanya vyadi and its management through Ayurveda-A Review - Bhardwaj, Anita; Kukkal, Sunita (International Research Journal of Ayurveda & Yoga, 2022)
Sthulta (Obesity) critical impacted on physical, mental and social wellbeing of a sufferer, could complicate mild diseases and a major reason of high mortality of a serious illness. Improper practicing of Ahar (diet) and Vihar (life style) are responsible to alter normal functioning of Agni consequently in place of Prasad bhag (nourishment), Ama (raw or toxin) is produced which has potency to disturb normal functioning by variating the Dosha, Dhatu and Mala thus cause various ailments. Three major forms of Agnis i.e., Jathragni, Bhutagni and Dhatuagni have potential to execute all bodily functions from cellular and systemic level. Dhatuagnis responsible for regular successive dhatu formation get power from Jathragni through bhutagni. Disturbing state of Agni may be of hypoactive, hyperactive or improper/disturbed type. In Sthulta hypoactive Medoagni cause to produce Ama meda which tend to accumulate and obstruct the Medovah strotas, which pollute internal environment. Sthulta is considered as chronic and hardly to cure type of ailment, therefore it has to be managed. Nidan parivarja, Aptarpana techniques, and Lekhaniya mahakashya help to assimilate Ama and normalise Meda dhatu. This article presents elaborated description of Sthulta, its causative factor Agni and details of management is explained through fundamentals mentioned in Ayurveda.